Assessing the home environment during mid- and late-adolescence. Issue 1 (2nd January 2019) - Bradley, Robert H.; Pennar, Amy; Fuligni, Andrew; Whiteside-Mansell, Leanne
ABSTRACT: The late adolescence version of the HOME Inventory (LA-HOME) documents actions, objects, events, and conditions connected with the home environment of children ages 16 and older still living at home. The study entailed a multi-stage process of measurement construction and validation that involved over 400 families from four states. The families were diverse by family composition, race/ethnicity, and socioeconomic status. Findings indicated expected relations between scores on six constituent domains of LA-HOME and measures of both family context and adolescent development. Relations varied across race/ethnic groups but were similar to those observed for the other four age-based versions of the HOME Inventory.